STING agonist enhances the efficacy of programmed death-ligand 1 monoclonal antibody in breast cancer immunotherapy by activating the interferon-β signalling pathway. Issue 8 (18th April 2022) - Yin, Mingming; Hu, Jinlong; Yuan, Zhongxu; Luo, Guangyi; Yao, Jiaming; Wang, Rundong; Liu, Dongquan; Cao, Baoqiang; Wu, Wenyong; Hu, Zhiqi
ABSTRACT: This study aimed to explore the role of a stimulator of interferon (IFN) gene (STING) agonist in breast cancer (BCa) immunotherapy. Clinical samples were collected from 37 patients with BCa. A tumor-bearing mouse model was established by injecting 4T1 cells into the mammary fat pad of mice. STING agonist and atezolizumab were injected in the mice twice a week for 2 weeks. Peripheral blood, tumor mass, lung, liver, brain cortex and kidney samples of the tumor-bearing mice were collected. Anti-IFN alpha receptor subunit 1 (IFNAR1) was used to treat 4T1 cells. Tumor tissues of patients with BCa exhibited lower STING and high programmed cell death protein 1 and programmed death-ligand 1 protein expressions. The STING agonist inhibited 4T1 cell growth in mice ( P < 0.001) and increased the IFN-β level and phosphorylation of STING, TBK1, IRF3 and STAT1 in tumor mass of tumor-bearing mice ( P < 0.001). It synergized with atezolizumab to inhibit 4T1 cell growth in mice and increased tumor necrosis factor-α, IFN-β, interleukin-10 and IFN-γ levels in the peripheral blood and tumor mass ( P < 0.01). It synergized with atezolizumab to increase CD8+ cytotoxic T cells and decrease FOXP3+ Treg cells in the tumor-bearing mouse model. The STING agonist was nontoxic to the lung, liver, brain cortex and kidney. Anti-IFNAR1 reversed the STING agonist promotion on TBK1, IRF3 and STAT1 phosphorylation in 4T1 cells ( P < 0.01). STING agonists enhance the efficacy of atezolizumab in BCa immunotherapy by activating the IFN-β signaling pathway.